2017
DOI: 10.1155/2017/8524985
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Helminths Infestation in Children Attending Princess Marie Louise Children’s Hospital in Accra, Ghana

Abstract: The deworming exercise program does not cover all children who are not in school. This study determined the prevalence and species type of helminth infestation and associated factors among children attending Princess Marie Louise Children's Hospital in Accra, Ghana. Children (225) below the age of 10 who have not taken antihelminthic drugs prior to the study period were recruited between May and June 2015. Children or guardians were interviewed using structured questionnaires and fresh stools were collected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 16 publications
6
22
2
1
Order By: Relevance
“…This finding is lower than a study conducted in different areas of Ethiopia, namely, in Jimma town 48.2% [ 23 ], 37%) [ 25 ], and 89.7% [ 26 ] in Wonji showa 24.3% [ 27 ], in Hawasa 26.6% [ 28 ], and in Gondar (34.2%) [ 29 ] and in Northwest Ethiopia 31.5% [ 30 ]. However, the prevalence of IPIs in the current study, was higher than studies conducted in Ghana 17.33% [ 31 ] and Brazil 17.5% [ 32 ]. The differences in finding among a range of studies could be explained by the methods employed for stool examination, diversity of health condition, water supply, feeding habit, cultural practices in the different study area, the study period, age variations, and geographical differences may have also contributed to the differences.…”
Section: Discussioncontrasting
confidence: 88%
“…This finding is lower than a study conducted in different areas of Ethiopia, namely, in Jimma town 48.2% [ 23 ], 37%) [ 25 ], and 89.7% [ 26 ] in Wonji showa 24.3% [ 27 ], in Hawasa 26.6% [ 28 ], and in Gondar (34.2%) [ 29 ] and in Northwest Ethiopia 31.5% [ 30 ]. However, the prevalence of IPIs in the current study, was higher than studies conducted in Ghana 17.33% [ 31 ] and Brazil 17.5% [ 32 ]. The differences in finding among a range of studies could be explained by the methods employed for stool examination, diversity of health condition, water supply, feeding habit, cultural practices in the different study area, the study period, age variations, and geographical differences may have also contributed to the differences.…”
Section: Discussioncontrasting
confidence: 88%
“…Similar results were found by Robert Mirisho by his study in Ghana it showed close relation between the practice of handwashing after use of toilet and prevalence of helminthic diseases in the children with margin of 0.04 times less likely to be infected by the worms. 24 In the study conducted by Gupta et al, the results have depicted that both rural and urban respondents have good knowledge on basic hand hygiene and it has been attributed to their usual understanding on personal as well as hand hygiene acquired from formal and informal learning processes. 25 In a Study conducted in Ethiopian children they had findings of need for more hand washing and hygiene education in schools and provide objective evidence that may guide the development of comprehensive health and hygiene intervention programs in rural Ethiopian schools.…”
Section: Discussionmentioning
confidence: 98%
“…Int J Contemp Pediatr. 2020 Jan;7(1):[24][25][26][27][28][29] International Journal of Contemporary Pediatrics | January 2020 | Vol 7 | Issue 1 Page 26 by the parents, 73% (n=267) washed their hands before meals, 22% (n= 75) after using the restroom(Figure 4).…”
mentioning
confidence: 99%
“…Hygiene refers to the personal practices and environment condition that help stop infection and the spread of it. Several studies suggest that the unhygienic practices such as not washing of hands, not bathing, untrimmed nails, eating food that fell on the ground, walking barefoot and not washing of hands after toilet use are risk factors of helminthiasis (Mascarini-Serra, 2011;Mengistu, Melaku, & Tesfu, 2014;Getnet, 2015;Mirisho, Neizer, & Sarfo, 2017;Schmidlin, Hurlimann, Silue et al, 2013;Suriptiastuti & Manan, 2016). Several studies have shown that health education about the cause and mode of infection of helminths, hygiene and sanitation practices and other health-related topics, are some of the strategies to combat this type of infection (Alelign, Degarege, & Erko, 2015;Alemu, Tegegne, Damte, & Melku, 2016;Getnet, 2015;Mengistu, Melaku, & Tesfu, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%